Financial Asset Holdings and Political Attitudes: Evidence from Revolutionary England. (6th May 2015) - Jha, Saumitra
Abstract: The English Parliament's struggle for supremacy against monarchical dictatorship during the Civil War (1642–1648) was crucial for the establishment of representative government, yet its lessons continue to be debated. I exploit novel data on individual MPs drawn from 1, 842 biographies to show that the conflict was over overseas interests and other factors over which the executive enjoyed broad constitutional discretion, rather than over domestic property rights. I further exploit the coincidence of individual MPs' ability to sign legally binding share contracts with novel share offerings by overseas companies to measure the effect of overseas share investment on their political attitudes. I show that overseas shareholding pushed moderates lacking prior mercantile interests to support reform. I interpret the effect of financial assetholding as allowing new investors to exploit emerging economic opportunities overseas, aligning their interests with traders. By consolidating a broad parliamentary majority that favored reform, the introduction of financial assets also broadened support for the institutionalization of parliamentary supremacy over dictatorial rule.